Virtual Reality: theoretical basis, practical applications - Philip Barker (Association for Learning Technology, 1993)
Virtual reality (VR) is a powerful multimedia visualization technique offering a range of mechanisms by which many new experiences can be made available. This paper deals with the basic nature of VR, the technologies needed to create it, and its potential, especially for helping disabled people. It also offers an overview of some examples of existing VR systems.